ANALISIS AKUNTANSI PIUTANG TRANSFER KE DAERAH DAN DANA DESA UAPBUN BA-999.05 - Deni Herdiyana (Politeknik Negeri Ambon, 2022)
The study was conducted to analyze the implementation of receivable accounting for transfer to the regions and village funds, and also comparing the accounting standards regarding transfers to the regions and village funds with the implementation carried out by UAPBUN BA-999.05. The research method used is a qualitative approach, namely literature study and descriptive analysis. The conclusion of the study is that in general the recognition, measurement, recording, presentation and assessment of TKDD have referred to the applicable regulations. However, there are differences in the recording of accounts for TKDD receivables transactions. Keywords: transfers to regions, village funds, TKDD receivables